Stability and Controlled Release of Amoxicillin Trihydrate in Novel Biopolymer Matrices - Malinee Namuangruk; Loilome Sriariyanun; Supawadee Prathep (Journal of Advances in Medicine and Pharmaceutical Sciences, 2025)
Amoxicillin trihydrate is a widely prescribed β-lactam antibiotic, suffers from chemical instability that limits its therapeutic efficacy and shelf life. This study investigates the formulation of controlled-release systems using locally sourced biopolymers in England, specifically alginate, chitosan, and pectin, to enhance drug stability and optimize release profiles. Microspheres were prepared via ionic gelation with varying polymer-to-drug ratios and characterized for particle morphology, thermal properties, crystallinity, and drug–polymer compatibility using SEM, DSC, XRD, and FTIR. Accelerated stability studies were conducted at 40°C and 75% relative humidity for 90 days, while in vitro release was assessed in simulated gastrointestinal fluids at pH 1.2 and 6.8. The results indicated that alginate–chitosan matrices provided superior encapsulation efficiency (>85%), structural integrity, and prolonged stability, reducing the degradation rate by up to fourfold compared to unencapsulated drug. Pectin-based formulations, although biodegradable, exhibited higher moisture sensitivity and faster initial drug release. In vitro release studies demonstrated a biphasic release pattern in alginate–chitosan systems, characterized by an initial burst followed by sustained release, predominantly governed by diffusion and polymer relaxation mechanisms. These findings highlight the potential of natural biopolymer matrices for improving the physicochemical stability and controlled release of amoxicillin, providing a sustainable alternative to conventional synthetic excipients. The study underscores the dual benefits of enhanced therapeutic performance and environmental sustainability, aligning with contemporary UK pharmaceutical priorities. Future work should explore in vivo pharmacokinetics and clinical translation to validate the therapeutic advantages of these formulations.